Syntheses, Crystal Structures and Spectroscopic Studies of Bis[1‐methyl‐3‐(methoxycarbonylmethyl)‐benzimidazolium]2+ [CuBr4]2− and [ZnBr4]2− Compounds. Issue 34 (4th December 2017) - Czekański, Łukasz; Hoffmann, Stanisław K.; Barczyński, Piotr; Gąsowska, A.; Zalewska, Alina; Goslar, Janina; Ratajczak‐Sitarz, Małgorzata; Katrusiak, Andrzej
Abstract: X‐ray diffraction structure of two new bis [1‐methyl‐3‐(methoxycarbonylmethyl) benzimidazolium] 2+ [CuBr4 ] 2− and [ZnBr4 ] 2− compounds has been determined. Zn‐crystal is monoclinic with perfect Td symmetry of the ZnBr4 tetrahedron, whereas the Cu‐compound is orthorhombic with D2d symmetry of CuBr4 tetrahedron. The difference in these structures is described as due to the static Jahn‐Teller effect. Vibrational spectroscopy (1800–3200 cm −1 ) identified hydrogen bond network. NIR‐UV‐Vis spectra (5000–50000 cm −1 ) are dominated by ligand‐to‐metal bands with d‐d transition contribution. EPR results (Q‐band) analyzed in terms of the MO‐theory showed a very strong delocalization of unpaired electron density on ligands accompanied by the Cu(II) 4pz orbital contribution. This effect is partially compensated by charge transfer transitions to the EPR g‐factor. Abstract : Novel compounds of benzimidazole derivative containing tetrahedral CuBr4 or ZnBr4 complexes have been synthesized. Static Jahn‐Teller effect deforming CuBr4 is responsible for differences in molecular packing and hydrogen bonds in these compounds. UV‐Vis spectrum is dominated by strong ligand‐to‐metal charge transfer bands characteristic for tetrahalidocuprates. EPR g‐factors were explained by considering the charge transfer and Cu(II) 4pz orbital mixing into the x 2 - y 2 ground state in terms of Molecular Orbital theory.